2021
DOI: 10.1101/2021.01.15.426556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell sequencing of theDrosophilaembryonic heart and muscle cells during differentiation and maturation

Abstract: The developing Drosophila heart consists of cardioblasts that differentiate into different types of cardiomyocytes and pericardial cells. A large body of work has identified numerous genes and pathways involved in heart specification and differentiation, downstream of cardiac transcription factors, such as Tinman (NKX2-5) and Dorsocross1/2/3 (TBX5). The advent of single-cell RNA sequencing (scRNAseq) technology allowed us for the first time to describe the transcriptome of different cardiac cell types in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…We next sought to understand if CHCHD3/6 has different temporal requirements for its effects on heart structure and function, since hearts of operated HLHS patients often develop reduced ejection fraction and heart failure, including the 11H proband. First, to assess whether CHCHD3/6 could have a role in early heart development, we mined embryonic heart-specific single-cell transcriptomic data (Vogler et al ., 2021) and found that CHCHD3/6 was expressed in Drosophila cardioblasts (CBs), along with other cardiogenic factors ( tinman , H15 , and Hand ) ( Figure 2A ). Next, we analyzed CHCHD3/6 mutant embryos for cardiac phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to understand if CHCHD3/6 has different temporal requirements for its effects on heart structure and function, since hearts of operated HLHS patients often develop reduced ejection fraction and heart failure, including the 11H proband. First, to assess whether CHCHD3/6 could have a role in early heart development, we mined embryonic heart-specific single-cell transcriptomic data (Vogler et al ., 2021) and found that CHCHD3/6 was expressed in Drosophila cardioblasts (CBs), along with other cardiogenic factors ( tinman , H15 , and Hand ) ( Figure 2A ). Next, we analyzed CHCHD3/6 mutant embryos for cardiac phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“… A) UMAP (uniform manifold approximation and projection) plot from CB-specific single-cell transcriptiomics (Vogler et al ., 2021) showing expression of CHCHD3/6 in CBs, as identified by cardiac TFs tin , H15 , and Hand . B) Stage 16-17 embryos (late stage cardiogenesis) were collected from a CHCHD3/6 loss of function line ( CHCHD D1 ) line crossed to a CHCHD3/6 deficiency line ( CHCHD DefA ) and stained for Mef2 (all muscle transcription factor, magenta) and Slit (secreted protein of the lumen, green).…”
Section: Resultsmentioning
confidence: 99%